Fungal rhinosinusitis in patient with multiple myeloma - case report - Anna Roszkowska; Tomasz Krzysztof Bąk; Jolanta Wojciechowicz; Anna Gawęda; Tomasz Tomaszewski (Kazimierz Wielki University, 2018)
It estimated that even one fifth of the general population may be affected by sinusitis. The significant increase of fungal rhinosinusitis over the last few years indicates the need of considering this diagnosis as possible in every patient affected by chronic rhinosinusitis. A case report of 58-year-old female treated displaying hematologic malignancy accompanied by chronic invasive sinusitis of maxilla is discussed herein.